The SNP, Scottish Labour and Glasgow 2014 – Contrasting Political Narratives of the 2014 Commonwealth Games. Issue 3 (August 2017) - Whigham, Stuart
Abstract : This article critically examines the predominant narratives which emanate from political discourse in relation to two significant events in Scotland in 2014 – the Glasgow Commonwealth Games and the independence referendum. This article uses an analysis of the political discourse from the two largest parties in the Scottish Parliament at the time of the Games, the pro-independence Scottish National Party (SNP) and the pro-union Scottish Labour Party, to highlight the contrasting discursive strategies of each party within their manifestos, policy documents, press releases and parliamentary speeches. This analysis demonstrates that each party portrayed nuanced positions on the Games, with the SNP illustrating the constraining nature of the constitutional status quo in relation to the potential economic and social benefits of the Games, and Labour using the event to illustrate the effectiveness of their stewardship of the Glasgow City Council despite the council funding cuts imposed by the SNP-led Scottish Government. Despite acknowledging the marginal status of the Games on the eventual outcome of the referendum, both parties suggested that the success of the event could lead to a 'feel-good factor' which could boost the 'Yes' vote. Such questionable claims are evaluated in light of past academic studies which question the validity of legacy outcomes from sporting events such as the Games (e.g.Giulianotti, 2016 ;Horne, 2007 ;Horne and Manzenreiter, 2006 ;Martin and Barth, 2013 ;Stewart and Rayner, 2016 ;Zimbalist, 2015 ).